Contribution of discourse and morphosyntax skills to reading comprehension in Chinese dyslexic and typically developing children - Chik, Pakey Pui-man (Springer US, 2010)
This study aimed at identifying important skills for reading comprehension in Chinese dyslexic children and their typically developing counterparts matched on age (CA controls) or reading level (RL controls). The children were assessed on Chinese reading comprehension, cognitive, and reading-related skills. Results showed that the dyslexic children performed significantly less well than the CA controls but similarly to RL controls in most measures. Results of multiple regression analyses showed that word-level reading-related skills like oral vocabulary and word semantics were found to be strong predictors of reading comprehension among typically developing junior graders and dyslexic readers of senior grades, whereas morphosyntax, a text-level skill, was most predictive for typically developing senior graders. It was concluded that discourse and morphosyntax skills are particularly important for reading comprehension in the non-inflectional and topic-prominent Chinese system.